2023
DOI: 10.1186/s13047-023-00678-0
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone replacement therapy is associated with increased odds of Achilles tendon injury and subsequent surgery: a matched retrospective analysis

J. Alex Albright,
Mary Lou,
Elliott Rebello
et al.

Abstract: Background Prescription of testosterone replacement therapy (TRT) has increased in the United States in recent years, and though anabolic steroids have been associated with tendon rupture, there is a paucity of literature evaluating the risk of Achilles tendon injury with TRT. This study aims to evaluate the associative relationship between consistent TRT, Achilles tendon injury, and subsequent surgery. Methods This is a one-to-one matched retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…For the quadriceps tendon, the TRT patients had an increased rate of tearing that was 5.8 times higher than the non-TRT control group. There was a 4.7 times higher rate of tears requiring repair 42 . The distal biceps study demonstrated that the TRT patients had a 4.1 times higher tear rate than the matched control group in the first year after starting TRT.…”
Section: Musculoskeletal Risks Of Trtmentioning
confidence: 89%
See 2 more Smart Citations

Testosterone

Arcand,
Poulin,
Testa
et al. 2024
JBJS Reviews
Self Cite
“…For the quadriceps tendon, the TRT patients had an increased rate of tearing that was 5.8 times higher than the non-TRT control group. There was a 4.7 times higher rate of tears requiring repair 42 . The distal biceps study demonstrated that the TRT patients had a 4.1 times higher tear rate than the matched control group in the first year after starting TRT.…”
Section: Musculoskeletal Risks Of Trtmentioning
confidence: 89%
“…Additionally in similar studies, the same group also showed increases in tendon ruptures and the need for surgical treatment of these injuries in other areas of the body [41][42][43] . For the quadriceps tendon, the TRT patients had an increased rate of tearing that was 5.8 times higher than the non-TRT control group.…”
Section: Complications Of Trtmentioning
confidence: 98%
See 1 more Smart Citation

Testosterone

Arcand,
Poulin,
Testa
et al. 2024
JBJS Reviews
Self Cite